The Effect Of The Flipped Classroom On Nursing Students’ Learning And Motivation Outcomes In Health Education - et. al., Mouna Hannaoui, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As contemporary society evolves, the technological revolution increasingly requires higher education institutions to adopt innovative strategies instead of traditional teaching. Improving the training of health professions in innovative teaching strategies would help prepare future nurses for professionalization. Therefore, the flipped classroom is one of the active educational approaches that has been shown to be effective on nursing students’ outcomes and motivation. Our study, spread over two years from 2018 to 2020, is a quantitative experimental pilot study, which aims to examine the effect of the flipped classroom on nursing students’ learning and motivation outcomes in health education of undergraduate nursing students of the ‘Higher Institute of Nursing Professions and Health Techniques’ (ISPITS). We used two tests, knowledge test and motivation test. The control group consisted of 15 students against 17 students from the experimental group. The experiment lasted three months. Our results showed a statistically highly significant (p<0.0001) increase (p<0.0001) in the grades and motivation levels of students in the experimental group. We point out that our experience coincided with the COVIC-19 pandemic which forced distance learning. According to our results, The flipped classroom could be an effective way to enhance the learning of nursing students and improve their motivation for knowledge to teach health sciencess